2015
DOI: 10.47210/bjohns.2015.v23i3.62
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Squamous Cell Carcinoma of External Acoustic Meatus Following Pigmented Basal Cell Carcinoma of Cheek -a Rare Occurrence

Abstract: Introduction: A synchronous second primary malignancy as squamous cell carcinoma of external acoustic meatus following basal cell carcinoma of cheek is reported with their management and review of literature. Case Report: Pigmented basal cell carcinoma of cheek was managed successfully by wide local excision followed by flap reconstruction and subsequently diagnosed squamous cell carcinoma of external acoustic meatus by concurrent chemoradiation after initial surgical debridement. Conclusion: Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…BCC exhibits a higher prevalence among males worldwide, likely due to greater UVR exposure [12][13][14][15]. Surprisingly, our study found a higher incidence among females, in line with some other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…BCC exhibits a higher prevalence among males worldwide, likely due to greater UVR exposure [12][13][14][15]. Surprisingly, our study found a higher incidence among females, in line with some other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, our study found a higher incidence among females, in line with some other studies. This discrepancy could be attributed to the fact that Indian housewives, especially rural women, are exposed to intermittent, intense UVR during household chores and fieldwork [14][15][16][17][18]. BCC primarily results from cumulative UVR exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al in such a rare case report opined that if surgery is needed for both the tumours, it can be done in a single stage in majority of the cases with low mortality and morbidity. 16 In our case too, we performed surgeries for both conditions in a single sitting.…”
Section: Discussionmentioning
confidence: 94%